Stokes-correlometric differentiation of polarization-heterogeneous images of biological tissues and some legal aspects of the use of early diagnosis of diseases - Гетманцев, Олександр Валентинович (My University, 2020)
This research contains the results: 1. of the method of Stokes-correlometric mapping, the physical processes of changes in optical anisotropy (distribution of optical axis directions and phase modulation) of biological structured (kidney) and parenchymal (liver) tissues of rat internal organs, which are caused by systemic pathology (diabetes), were identified and analyzed as part of a statistical analysis. 2. of the most sensitive parameters (statistical moments of the 1st – 4th orders of magnitude, the correlation moment of the 4th order) to changes in the distribution structure of the magnitude and phase of the SCS of the 3rd and 4th parameters of the “two-point” parameter of the Stokes polarization heterogeneous microscopic images of histological sections of healthy and diabetic rat kidney and liver tissues. 3. of social and legal aspects of implementation of methods for early diagnosis of systemic diseases in public society.
Keywords: Stokes-correlometry, wavelet analysis, spatial-frequency filtering, biological tissues